ENSEFALITIS ANTIRESEPTOR NMDA ENSEFALITIS DENGAN GEJALA AWAL PSIKOSIS - Riwanti Estiasari,* Darma Imran,* Kartika Maharani,* David Pangeran,* Fitri Octaviana,* Dewi Wulanda (NEURONA, 2017)
ANTI NMETHYLDASPARTATE NMDA RECEPTOR ENCEPHALITIS IS SELDOM FOUND IN INDONESIA THE ATYPICAL INITIAL PRESENTATION OF PSYCHOSIS AND COGNITIVE DISTURBANCE RESULTS IN UNDERDIAGNOSED OR EVEN UNDIAGNOSED CASE THIS REPORT DESCRIBED A 12YEAROLD GIRL PRESENTING WITH INITIAL PSYCHIATRIC SYMPTOM FOLLOWED BY SEIZURE AND OROPHARYNGEAL DYSTONIA